Bi‐2223 grain growth in Ag/Ni composite‐sheathed tapes sintered at different oxygen partial pressures. Issue 8 (25th March 2015) - Chen, X. P.; Li, X. G.; Liu, M.; Wang, B.; Liu, Q.
<x xml:space="preserve">Abstract</x> Bi‐2223 ceramic grain growth in Ag/Ni composite‐sheathed tapes sintered at different oxygen partial pressures was investigated systematically. The effect of oxygen partial pressure on the evolution of phases, texture, and microstructure development in tapes was characterized by X‐ray diffraction and scanning electron microscope. Development curves of Bi‐2223 phase at different oxygen partial pressures were different, indicating that they were in different formation stages of Bi‐2223 during the sintering period. The appearance time of optimized texture in Bi‐2223/Ag/Ni tapes was influenced greatly by oxygen partial pressure, which had an essential effect on Bi‐2223 formation and growth. Grain size in nonfully reacted tapes sintered at higher oxygen partial pressure was smaller than that in tapes sintered at lower oxygen partial pressure, which was opposite to the result in fully reacted tapes. Depending on the above results, growth process of Bi‐2223 platelets at different oxygen partial pressures was expounded in detail combined with kinetics.